Internet of Things. Information Processing in an Increasingly Connected World First IFIP International Cross-Domain Conference, IFIPIoT 2018, Held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-19, 2018, Revised Selected Papers - Strous, Leon; Cerf, Vinton G. (IFIP Advances in Information and Communication Technology,, 2019)
This book is open access under a CC BY 4.0 license.